Power/Knowledge in George Orwell’s 1984 and Eiichiro Oda’s One Piece: A Foucauldian Comparative Analysis - Widanarti Widanarti; Agry Pramita; Bunyamin Faisal Syarifudin (GLENS: Global English Insights Journal, 2026)
This qualitative comparative study examines how power operates through the control of knowledge in George Orwell's 1984 and "The Tragedy of Ohara" arc, Chapters 391–398 of Volume 41 of Eiichiro Oda's One Piece, analyzed using the official VIZ Media English translation. Following Sapardi Djoko Damono's comparative literature approach within Michel Foucault's power/knowledge framework, data were purposively selected using three criteria: explicit depiction of knowledge-control mechanisms, correspondence to one of four analytical aspects (control of information, production of knowledge, construction of truth, and exercise of power through discourse), and relevance to the comparative aims. Close reading and deductive, theory-driven coding were applied to quotations, dialogue, and manga panels. The findings show that both works represent knowledge as the primary object of politicaal control across all four aspects, yet differ in mechanism: 1984 sustains concealed, continuous, bureaucratic control through historical revision and language manipulation, whereas "The Tragedy of Ohara" enacts an overt, singular act of institutional violence through censorship, propaganda, and destruction of knowledge producers. Rather than extending Foucault's framework theoretically, the study demonstrates its continued applicability across cultural and medial boundaries, offering a modest contribution confined to these two texts rather than a generalizable claim about dystopian fiction or manga.